2019
DOI: 10.1038/s41598-019-52644-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BMI on peak growth hormone responses to provocative tests and therapeutic outcome in children with growth hormone deficiency

Abstract: This study investigated the relationship between peak stimulated growth hormone (GH) and body mass index (BMI), as well as the impact of BMI on therapeutic response in patients with GH deficiency (GHD). A total of 460 patients were enrolled in the study. The patients were divided into four groups as per the etiology and peak GH values: idiopathic (n = 439), organic (n = 21), complete (n = 114), and partial (n = 325) GHD groups. Subsequently, they were classified as normal, overweight, or obese based on their B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
2
24
0
1
Order By: Relevance
“…Indeed, height SDS was statistically lower in females (mean height SDS: -2.65 ± 0.85) than males (-2.32 ± 0.94, p value of 0.02). Finally, the demonstrated negative correlation between BMI-SDS and GH peaks has been already widely described (31). In our study population, GH ITT and GH DST cohorts were statistically homogeneous in terms of baseline BMI-SDS levels and did not differ with reference to the negative effect of BMI on the GH peaks elicited by both ITT and DST, with a 5% and 6% drop in GH peaks for 1 BMI-SDS increase, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, height SDS was statistically lower in females (mean height SDS: -2.65 ± 0.85) than males (-2.32 ± 0.94, p value of 0.02). Finally, the demonstrated negative correlation between BMI-SDS and GH peaks has been already widely described (31). In our study population, GH ITT and GH DST cohorts were statistically homogeneous in terms of baseline BMI-SDS levels and did not differ with reference to the negative effect of BMI on the GH peaks elicited by both ITT and DST, with a 5% and 6% drop in GH peaks for 1 BMI-SDS increase, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…It is well known that the secretion of GH is significantly reduced in obese individuals compared to age-matched controls 40 . Given the clear relationship between BMI and peak stimulated GH demonstrated in short stature, our findings are consistent with previous studies 6 , 7 . We found a negative association between BMI and peak GH in children with short stature.…”
Section: Discussionsupporting
confidence: 93%
“…However, GH secretion is regulated by multiple physiologic factors, including age, sex, body mass index (BMI) and onset of puberty, which sometimes may produce false-positive results 2 4 . Previous studies have demonstrated that obese children and adolescents have a reduced stimulated GH response to provocative testing 5 , and it is well known that there is a significant negative association between BMI and peak GH 6 , 7 . Furthermore, insulin resistance (IR) has been demonstrated to be involved in the relationship between BMI and reduced growth hormone secretion 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the relationship between BMI SDS and peak GH in children. [16][17][18][19][20] Although each study used different number of subjects, different period of study or different number of stimulant used for analysis, they all demonstrated the relationship between BMI SDS and peak serum GH in common.…”
Section: Discussionmentioning
confidence: 99%